Overall benefits of smoking cessation in patients with ASCVD are underestimated. (11th May 2022) - Van Trier, T; Snaterse, M; Hageman, SHJ; Ter Hoeve, N; Sunamura, M; Moll Van Charante, EP; Galenkamp, H; Deckers, JW; Visseren, FLJ; Scholte Op Reimer, WJM; Peters, RJG; Jorstad, HT
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: New risk prediction models estimate and employ individual 'treatment benefit', which can be used to motivate patients with atherosclerotic cardiovascular disease (ASCVD) to quit smoking and to adhere to beneficial pharmacological interventions. However, this treatment benefit is usually calculated for a limited set of cardiovascular outcomes, i.e. years gained without myocardial infarction or stroke, while ignoring non-cardiovascular health benefits and pharmacological side- and adverse effects. Importantly, treatment effect size of medication is smaller in persistent smokers compared to non-smokers, because of the higher overall mortality of the smokers. By disregarding non-cardiovascular outcomes, the overall benefit of smoking cessation will be underestimated. Purpose: We estimated and compared the treatment benefits – expressed as 'gain in years without major cardiovascular events' – of smoking cessation versus persistent smoking with targeted pharmaceutical interventions in patients with established ASCVD treated with anti-platelet agents, statins and anti-hypertensive drugs. Methods: We pooled individual-level risk factors data from six large, recent prospective studies: RESPONSE 1 and 2, OPTICARE, EUROASPIRE IV and V and HELIUS. We included patients aged ≥45 years who persisted in smoking ≥6 months after acute coronary syndrome or revascularisation. The primary outcome was SMART-REACH estimated treatment benefit expressed as gain in years without a myocardial infarction or stroke. We compared the cardiovascular treatment benefit of smoking cessation versus the use of one or more pharmaceutical treatments: bempedoic acid, colchicine and PCSK9 inhibitors. Results: We included 989 smokers with established ASCVD (23% female), with mean age of 60 (SD 8) years at median 1.2 (IQR 1.0-2.0) years post-index event. A mean of 4.81 (95%CI 4.73-4.89) event-free years would be gained through smoking cessation. Persistent smoking with maximal pharmaceutical treatment resulted in a comparable gain of 4.83 (95% CI 4.72-4.93) event-free years.(Figure) Conclusion: The estimated lifetime treatment benefit of smoking cessation appeared to be comparable to the use of several pharmaceutical treatments combined, even when the analysis was limited to major cardiovascular events. This substantial health benefit underscores smoking cessation to be one of the most important actions to improve the overall health of patients with established ASCVD. To accurately compare treatment options, overall benefits and harms should be considered, in addition to the patients' preferences, in a shared decision making process.